ANALYSIS OF WEIBULL PARAMETERS FOR WIND POWER GENERATION - Oliveira Filho, O. D. Q. de; Araújo, A. M.; Borges, W. F. A.; Silva, A. A. C.; Bezerra, C. C. A.; Fernandes, E. C. R.; Rocha, E. J. F.; Rocha, G. J. A. M.; Andrade, L. I.; Ribeiro, D. G. (Revista de Engenharia Térmica, 2018)
The aim of the present work is to perform an analysis of both Weibull parameters k and c for wind power generation so that one can have an idea of how the mechanisms of wind energy estimation work and build a better understanding of these parameters. This paper covers aspects from the definition of continuous random variable to the analysis of the scale (c) and shape (k) parameters themselves. Mathematical and physical analysis will be performed and finally, a comparison between the parameters and their influence on wind analysis will be presented.